(Paramount urdu silsila )Karwan-e-urdu class 4 - Professor ali akbar (Paramount Books (Pvt.) Ltd; Lahore, 2015)
Karwan-e-Urdu by Professor Ali Akbar is a literary journey through the rich history, evolution, and nuances of the Urdu language, highlighting its cultural significance.